The Influence of Visionary Leadership, Digital Marketing, and Digital Culture on Competitiveness at Institut Agama Islam Negeri (IAIN) Takengon - Didi Sartika; Amiruddin Siahaan; Masganti (Tadbir : Jurnal Studi Manajemen Pendidikan, 2026)
This study aims to analyze the influence of visionary leadership, digital marketing, and digital culture on competitiveness at the State Institut Agama Islam Negeri (IAIN) Takengon. This study is motivated by the importance of digital transformation in Islamic higher education in order to remain competitive in a global era full of technological disruption. This research uses a quantitative approach with the Structural Equation Modeling – Partial Least Squares (SEM-PLS) method. The research population consists of all lecturers within the IAIN Takengon environment, with the sample determined using a purposive sampling technique. The research instrument is a questionnaire using a Likert scale that has been tested for validity and reliability. The results show that visionary leadership has a direct and significant effect on competitiveness (β = 0.223; p = 0.012) with a contribution of 22.3%. Digital marketing also has a direct effect on competitiveness (β = 0.293; p = 0.001) with a contribution of 29.3%. The most dominant factor is digital culture, which provides a direct and significant effect on competitiveness (β = 0.418; p = 0.000) with a contribution of 41.8%. In addition, visionary leadership is proven to have a significant effect on digital culture (β = 0.430; p = 0.000) with a contribution of 43.0%, and digital marketing also affects digital culture (β = 0.440; p = 0.000) with a contribution of 44.0%. Indirect effects were also found, namely visionary leadership on competitiveness through digital culture (β = 0.180; p = 0.005) with a contribution of 18.0%, and digital marketing on competitiveness through digital culture (β = 0.184; p = 0.002) with a contribution of 18.4%. Simultaneously, the three independent variables (visionary leadership, digital marketing, and digital culture) are able to explain competitiveness by 67.5% (R² = 0.675), while the remaining 32.5% is influenced by other factors outside the research model.